1994
DOI: 10.1177/104063879400600405
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-based Test for the Specific Identification of Mycoplasma Mycoides Subspecies mycoides SC

Abstract: Abstract. The polymerase chain reaction (PCR) was used to develop a test for the detection of Mycoplasma mycoides subspecies mycoides SC in the tissues of animals infected with contagious bovine pleuropneumonia (CBPP). Two sets of primers were designed; one set (MC323/MC358) to amplify a ~1.5-kbp DNA fragment from all the members of the M. mycoides 'Cluster' and the other set (MM450/MM451) specifically amplified a 574-bp DNA fragment from M. mycoides subspecies. The PCR products could be differentiated further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 7 publications
2
51
0
2
Order By: Relevance
“…The oligonucleotide primer pair MMMSCO5-7 and MMMSCO5-6 can therefore be used in a confirmatory PCR method for the genetic identification of M. mycoides subsp. mycoides SC, together with previously established methods (6,13,24). It must be noted that no DNA sequence with similarity to that of lppQ has been found in other species of the class Mollicutes, based on currently accessible DNA sequences in databases.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotide primer pair MMMSCO5-7 and MMMSCO5-6 can therefore be used in a confirmatory PCR method for the genetic identification of M. mycoides subsp. mycoides SC, together with previously established methods (6,13,24). It must be noted that no DNA sequence with similarity to that of lppQ has been found in other species of the class Mollicutes, based on currently accessible DNA sequences in databases.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst serological classification and differentiation of cluster members is difficult, it has been shown that they can be distinguished by DNAbased diagnostic methods. The CAP-21 genomic region was used by Taylor et al (1992) to design a DNA probe identifying M. mycoides subspecies and also a PCR assay for identification of the SC type (Bashiruddin et al, 1994). Hotzel et al (1996) developed a PCR system for differentiation of all cluster groups which exploited nucleotide sequence variations in the same region.…”
mentioning
confidence: 99%
“…The use of molecular tests directly on clinical specimens may improve the sensitivity of testing as the tests are not reliant on containing viable bacteria. However, the use of specific PCRs, such as the M. conjunctivae PCR and the Mycoplasma ''mycoides cluster'' and Mycoplasma ''mycoides subcluster'' PCRs coupled with restriction fragment length polymorphisms (Bashiruddin et al, 1994) will only detect and identify the specific Mycoplasma species the investigator is targeting and requires the use of several different tests. The recently introduced PCR/DGGE FIGURE 3.…”
Section: Discussionmentioning
confidence: 99%